Intersectional equity in health care: assessing complex inequities in primary and secondary care utilization by gender and education in northern Sweden - Fortune N. Nyamande; Paola A. Mosquera; Miguel San Sebastián; Per E. Gustafsson (BMC, 2020)
Abstract Background Knowledge remains scarce about inequities in health care utilization between groups defined, not only by single, but by multiple and intersecting social categories. This study aims to estimate intersectional horizontal inequities in health care utilization by gender and educational level in Northern Sweden, applying a novel methodological approach. Methods Data on participants (N = 22,997) aged 16-84 years from Northern Sweden came from the 2014 Health on Equal Terms cross sectional survey. Primary (general practitioner) and secondary (specialist doctor) health care utilization and health care needs indicators were self-reported, and sociodemographic information came from registers. Four intersectional categories representing high and low educated men, and high and low educated women, were created, to estimate intersectional (joint, referent, and excess) inequalities, and needs-adjusted horizontal inequities in utilization. Results Joint inequalities in primary care were large; 8.20 percentage points difference (95%CI: 6.40-9.99) higher utilization among low-educated women than high-educated men. Only the gender referent inequity remained after needs adjustment, with high- (but not low-) educated women utilizing care more frequently than high-educated men (3.66 percentage points difference (95%CI: 2.67-5.25)). In contrast, inequalities in specialist visits were dominated by referent educational inequalities, (5.69 percentage points difference (95%CI: 2.56-6.19), but with no significant horizontal inequity - by gender, education, or their combination - remaining after needs adjustment. Conclusion This study suggests a complex interaction of gender and educational inequities in access to care in Northern Sweden, with horizontal equity observable for secondary but not primary care. The study thereby illustrates the unique knowledge gained from an intersectional perspective to equity in health care.